Adenosine Deaminase (ADA) Analysis In Pleural Fluid: A Diagnostic Tool For Tuberculous Pleurisy: Adenosine Deaminase (ADA) Analysis In Pleural Fluid: A Diagnostic Tool For Tuberculous Pleurisy - Malek, Dr Saklainhaider S; Patel, Dr Shirishkumar M; Desai, Dr Kairavi J (National Journal of Integrated Research in Medicine, 2019)
Objective: Tuberculous pleurisy is categorised as extra-pulmonary despite an intimate anatomic relationship between pleura and the lungs. The diagnosis of tuberculous pleurisy is often difficult. A reliable, cost effective and rapid diagnostic test, which can be performed in any routine laboratory, could be of help in the diagnosis of tuberculous pleurisy. In the present study we measured the adenosine deaminase (ADA) activity in pleural fluid of tuberculous pleurisy and non tuberculous pleurisy patients. Method: ADA activity in pleural fluid was determined according to a method based on the modified Berthlot reaction, which is the formation of a colour indophenol complex from ammonia liberated from adenosine, and quantified spectrophotometrically. Results: ADA activity was studied in pleural fluid of 106 cases of suspected tuberculous pleural effusions. Culture for M.tuberculosis was positive in 43 cases, while in 63 cases culture was negative. From 49 ADA test positive samples 43 were culture positive and 6 were culture negative. The higher level of ADA in tuberculous pleurisy was statistically highly significant (p < 0.00001). The sensitivity and specificity of ADA test in pleural fluid was 100% and 90.47% respectively. Conclusion: This study demonstrated that adenosine deaminase activity in pleural fluid, a relatively inexpensive and easy procedure, can be of great value in the diagnosis of tuberculous pleurisy. This test can be performed in any routine laboratory where more sophisticated methods are not available.